Using complementary grouping strategy for cooperative learning. (1st January 2014) - Wu, YuLung
Grouping strategy plays a pivotal role in cooperative learning. The grouping strategy affects the learning performance of these grouping teams. As widely conferred upon in previous literature, the heterogeneous group is an effective means of cooperative learning. This study presents a grouping strategy based on the knowledge structure diagram and learning portfolio. The knowledge structure diagram represents student knowledge structure. The knowledge structure diagram and learning portfolio is used to calculate the score of cooperation and interaction that represents not only homogeneous relationship but also mutual complementarily. The present grouping strategies have been adopted in a course – 'database system'. The evaluation raised by this study has gotten positive experimental results. The proposed system helps teachers to understand a large number of students and remind the weakness of students.